Learning from the Climate Change Debate to Avoid Polarisation on Negative Emissions. Issue 1 (2nd January 2020) - Colvin, R. M.; Kemp, Luke; Talberg, Anita; De Castella, Clare; Downie, C.; Friel, S.; Grant, Will J.; Howden, Mark; Jotzo, Frank; Markham, Francis; Platow, Michael J.
ABSTRACT: This paper identifies critical lessons from the climate change experience to guide how communications and engagement on negative emissions can be conducted to encourage functional public and policy discourse. Negative emissions technologies present a significant opportunity for limiting climate change, and are likely to be necessary to keep warming below 2°C. While the concept of negative emissions is still in its infancy, there is evidence of nascent polarization, and a lack of nuance in discussion of individual technologies. We argue that if negative emissions technologies are to be implemented effectively and sustainably, an effective governance regime is needed; built on functional societal discourse and avoiding the ideological baggage of the broader climate change debate or the controversies concerning geoengineering. At its core, our argument is to avoid the ideological bundling of negative emissions; this can be pursued directly and via careful selection of communication frames and the use of non-partisan, trusted messengers. Whether these lessons are heeded may determine if negative emissions are governed proactively, or are distorted politically, misused and delayed.